Low-dose cyclosporine in treatment of membranous nephropathy with nephrotic syndrome: effectiveness and renal safety. (1st January 2017) - Yu, Xiaojuan; Ruan, Lin; Qu, Zhen; Cui, Zhao; Zhang, Yimiao; Wang, Xin; Meng, Liqiang; Liu, Xiaojing; Wang, Fang; Zhang, Ying; Liu, Gang; Yang, Li
Abstract: Background: To observe effectiveness and renal safety of long-term low-dose cyclosporine in idiopathic membranous nephropathy (IMN). Methods: Sixty-eight patients were enrolled in this prospective cohort study. Renal endpoint was defined as a decrease in eGFR ≥50% from baseline and a development of eGFR ≤60 ml/min/1.73m 2 . Results: A cyclosporine dose of 2.0 ± 0.5 mg/kg/d and a prednisone of 0.3 ± 0.2 mg/kg/d were prescribed. The duration of cyclosporine treatment was 27 (3–80) months. The overall remission rate was 91% with a relapse rate of 42%. Fourteen patients had cyclosporine-related acute renal injury (CsA-ARI) within the first three months, and 16 patients had cyclosporine related chronic renal injury (CsA-CRI) within the first year. At the end of follow-up (50 ± 18 months), 16 patients (24%) reached renal endpoint. Presence of intimal fibrosis of small artery and higher time-averaged proteinuria were identified as independent risk factors for renal endpoint. RAS inhibition treatment decreased the risk of poor renal outcome. Patients in CsA-ARI group had the highest proteinuria at the third month, the highest time-average proteinuria and the highest proportion of cases reaching renal endpoint. Patients with CsA-CRI were of the oldest age and with the lowest baseline eGFR. Conclusions: Low-dose cyclosporine is effective in treating IMN. CsA-ARI and no response in proteinuria during the first three months of cyclosporine treatment had the lowest benefit/risk ratio, and these patients should be switched to non-calcineurin-inhibitor based regimen. Patients of older age, with lower baseline eGFR, or having intimal sclerosis of small artery, are more likely to develop progressive renal dysfunction.